Phase I/II study of bendamustine in combination with ofatumumab, carboplatin, etoposide (BOCE) for relapsed or refractory aggressive B-cell non-Hodgkin lymphoma. Issue 3 (23rd February 2021) - Pan, Jonathan; Ghimire, Sushil; Alpdogan, S. Onder; Chapman, Andrew; Carabasi, Matthew; DiMeglio, Martina; Gong, Jerald; Martinez-Outschoorn, Ubaldo; Rose, Lewis; Ramirez, Michael; Wagner, John L.; Weiss, Mark; et al.
Abstract: We developed an outpatient salvage chemotherapy regimen using bendamustine, ofatumumab, carboplatin and etoposide (BOCE) to treat relapsed/refractory non-Hodgkin lymphoma (RR NHL) in a single-center phase I/II study. Primary objectives were safety, tolerability and overall response rate (ORR). Thirty-five RR NHL patients (57% de novo large cell [DLBCL] or grade 3B follicular [FL], 26% transformed DLBCL, 9% grade 3A FL, 3% mantle cell; median age = 62, median prior therapies = 1) were treated. Median follow-up was 24.1 months. ORR was 69% (CR = 49%, PR = 20% [ORR = 70%, CR = 50%, PR = 20% in the de novo DLBCL/grade 3B FL subgroup]). Median progression-free survival was 5.1 months and overall-survival 26.2 months. Twelve patients subsequently underwent stem cell transplantation. The most common non-hematologic grade 3–4 toxicities were neutropenic fever and hypophosphatemia. There were no treatment-related deaths. In conclusion, BOCE is a safe and effective outpatient salvage regimen for patients with RR NHL and serves as an effective bridge to stem cell transplantation.